Some correlations between interest and willingness to pay - Kálmán Botond Géza; Калман Ботонд Гейзо; Poyda-Nosyk Nina; Пойда-Носик Ніна; Pojda-Noszik Nina; Robert Bacho; Бачо Роберт; Bacsó Róbert; Kobla Sewornu Afadzinu; Кобла Севорну Афадзіну; Malatyinszki Szilárd; Малатінскі Сілард; et al. (EnPress Publisher LLC, 2025)
Abstract. This article delves into the causes of the 2008 financial crisis, particularly focusing on its inception marked by the collapse of the mortgage market, which cascaded into the bankruptcy of numerous banks. The crisis stemmed from volatile real estate prices, leading to loans being issued to borrowers without sufficient collateral, exacerbating insolvency. In Hungary, the situation was exacerbated as most housing loans were denominated in Swiss francs, causing repayment obligations to soar due to rapid fluctuations in the exchange rate. State intervention became imperative amidst rising insolvency rates. Motivated by a longstanding interest in the economic ramifications of low interest rates, the authors aim to probe the factors influencing loan repayment motivations. Their research centers on the evolution and functions of state interest rate regulation, while also scrutinizing late fees and interest provisions related to tax and civil law claims to evaluate their impact on timely payments. Embracing an interdisciplinary approach blending historical, economic, and legal perspectives, the article underscores the necessity for well-calibrated regulatory interventions to mitigate the excesses of unrestricted free markets, especially in light of evolving global economic dynamics. It also underscores the importance of prudent regulations, given theories suggesting that persistently low interest rates may lead to economic distortions beyond a certain threshold, while acknowledging the constraints of interest rate adjustments.
Editorial Board: https://systems.enpress-publisher.com/index.php/jipd/about/editorialBoard Table of Contents: https://systems.enpress-publisher.com/index.php/jipd/issue/view/415
Keywords: debt; exchange rate; interest; nonperforming loans; repayment